ReProDB Web Application (Research Project Database) / Jennifah Nordin ... [et al.] - Nordin, Jennifah; Arapa, Afida; Anthony Aning, Ibianaflorinciliana Niane; Azizan, Intan Syahriza (2021)
At undergraduate and postgraduate levels, most universities required students to do research projects and submitted the report to the faculty for marking and record purposes. The current practice is most universities will keep all research projects or selected ones in their library departments or their faculty offices. Some universities required the students to submit their report in a soft copy by downloading it in CD. This practice required sufficient space and involved cost in purchasing office cabinets or racks. In addition, while using CD, it will expose data being corrupted or damaged. Moreover, some research will become wasted since the research knowledge or data is not being kept properly. At the same time, every semester new batch of students needs to submit their report, which required more space to keep it. To overcome this issue and embrace the technology, the group proposed a project, namely "ReProDB Web Application (Research Project DataBase)" The project aims to create a database to keep all student's research project reports, reduce clerical tasks or administrative tasks among the administrator, and have one research database that all researchers and their supervisors can turn to. Thus, the database is expected to save space and energy, less administrative work among administration staff, faculty members, and the research facilitator. Furthermore, it's also foreseen as one effort which is not only able to reduce the cost of printing and purchasing office equipment but also cost of recruitment and emolument cost. Nevertheless, it is an organized web-based system or application that is designed to maintain long-term access to digital data which greatly increase efficiency in data/record management which becomes as an organization's information asset.